Russian Faith Matters: Religiosity and Civil Society in the Russian Federation. (1st June 2018) - Mersianova, Irina V; Schneider, Frederick A
Abstract: Inspired by recent studies of the relationship between religiosity and norms of civic participation in the West, the authors examined four areas of possible correlation between similar norms and values in contemporary Russian society: authoritarianism, charitable giving, volunteering, and support for NGOs. The authors obtained survey responses from 1, 500 randomly selected Russian citizens from 105 urban and rural locations in 43 regions across the Russian Federation. Results emphasize that in Russia, as in much of the developed world, active religious attendance matters and that the impact of such behavior in Russia is generally prosocial, not authoritarian, and possibly driven by the moral discourses found in religious communities. Results also suggest that the impact of religiosity in Russia is diminished by the relatively small segment of the population that claims regular religious attendance. Together these results highlight the importance of further studies of pious Russians' behavior and beliefs.